PENGARUH PRESTASI BELAJAR, PENDAPATAN ORANG TUA, DAN EKSPEKTASI KERJA TERHADAP MINAT MELANJUTKAN STUDI S2 PADA MAHASISWA PROGRAM STUDI PENDIDIKAN EKONOMI UNIVERSITAS PGRI WIRANEGARA - M. Syarifudin; Nunuk Indarti; Sugeng Pradikto (Cendikia: Jurnal Pendidikan dan Pengajaran, 2023)
This study aims to determine the effect of learning achievement, parental income, and work expectations on interest in continuing S2 studies in students of the Economic Education Study Program, PGRI Wiranegara University. This research is a quantitative research with causal associative method. The population in this study is 94 students of the Economic Education Study Program of PGRI Wiranegara University batch 2019 and 2020. The data collection techniques used are questionnaires and documentation, with prerequisite tests, namely classical assumption tests including: (normality, linearity, multicollinearity, heteroscedasticity). The data analysis method used is multiple linear regression analysis. The results obtained in this study show that: (1) there is a partial positive and significant influence of learning achievement on interest in continuing S2 studies. (2) there is a partial positive and significant influence on parents' income on interest in continuing S2 studies. (3) there is a partial positive and significant influence on work expectations on interest in continuing S2 studies. (4) there is a simultaneous positive and significant influence on learning achievement, parental income, and work expectations on the interest in continuing S2 studies on students of the Economic Education Study Program, PGRI Wiranegara University. Based on the results of the coefficient of determination (R2) of 0.879 or 87.9% which shows that 87.9% of interest in continuing S2 studies is influenced by learning achievement, parental income and work expectations. While the remaining 12.1% was influenced by other variables that were not studied in this study.